The Militia and the Right to Arms, or, How the Second Amendment Fell Silent - Uviller, H. Richard; Merkel, William G., 1965- (Book collections on Project MUSE., 2002)
"A well regulated Militia, being necessary to the security of a free State, the right of the people to keep and bear Arms, shall not be infringed."--Amendment II, United States ConstitutionThe Second Amendment is regularly invoked by opponents of gun control, but H. Richard Uviller and William G. Merkel argue the Amendment has nothing to contribute to debates over private access to firearms. In The Militia and the Right to Arms, or, How the Second Amendment Fell Silent, Uviller and Merkel show how post-ratification history has sapped the Second Amendment of its meaning. Starting with a detailed examination of the political principles of the founders, the authors build the case that the Amendment's second clause (declaring the right to bear arms) depends entirely on the premise set out in the Amendment's first clause (stating that a well regulated militia is necessary to the security of a free state). The authors demonstrate that the militia envisioned by the framers of the Bill of Rights in 1789 has long since disappeared from the American scene, leaving no lineal descendants. The constitutional right to bear arms, Uviller and Merkel conclude, has evaporated along with the vanished universal militia of the 18th century. Using records from the founding era, Uviller and Merkel explain that the Second Amendment was motivated by a deep fear of standing armies. To guard against the debilitating effects of militarism, and against the ultimate danger of a would-be Caesar at the head of a great professional army, the founders sought to guarantee the existence of well-trained, self-armed, locally commanded citizen militia, in which service was compulsory. By its very existence, this militia would obviate the need for a large and dangerous regular army. But as Uviller and Merkel describe the gradual rise of the United States Army and the National Guard over the last two hundred years, they highlight the nation's abandonment of the militia ideal so dear to the framers. The authors discuss issues of constitutional interpretation in light of radically changed social circumstances, and contrast their position with the arguments of a diverse group of constitutional scholars including Sanford Levinson, Carl Bogus, William Van Alstyne, and Akhil Reed Amar. Espousing a centrist position in the polarized arena of Second Amendment interpretation, this book will appeal to those wanting to know more about the Amendment's relevance to the issue of gun control, as well as to those interested in the constitutional and political context of America's military history.